Wireless Channel Characterization for Indoor Environment in Thermal Power Plant. Issue 11 (November 2016) - NABETANI, TOSHIHISA; YABU, HIROKI; OHKUMA, EIICHI; FUKUI, MAMORU
SUMMARY: Wireless communications in industrial environments are seriously affected by reliability and performance issues, due to the multipath nature of obstacles within such environments. In order to utilize wireless systems for machine‐to‐machine applications in industrial environments, it is necessary to investigate and model their channel characteristics for optimal design and reliability assessment. However, the wireless channel characterization in such environments has not been sufficiently addressed in the literature within the scope of our knowledge. In this paper, to shed light on the channel modeling for plant applications, we measure and analyze the indoor channel characteristics in a typical thermal power plant. Our results indicate that the channel characterization of the plant environment is specific when compared with the general environments such as houses and offices. The findings in this paper provide a useful guidance to the design of wireless system for the realization of reliable control systems in power plants.